1942
DOI: 10.1017/s0022172400012596
|View full text |Cite
|
Sign up to set email alerts
|

The administration of vitamin C in a large institution and its effect on general health and resistance to infection

Abstract: 1. The vitamin C in the dietary of an institution was largely destroyed by the methods of cooking and distribution.2. Some 50 mg. of ascorbic acid per head per day were required to be added to the diet to produce an optimum excretion level.3. Large doses of ascorbic acid were given to a group of adolescents in the institution over a period of several months. A record was kept of the incidences of infectious diseases in this treated group and in the remainder (controls). The following conclusions were reached:(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

1944
1944
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 54 publications
0
34
1
Order By: Relevance
“…In any case, this particular study yielded no evidence for benefit either from L-ascorbic acid, or from L-ascorbic acid plus Disoascorbic acid. Hemilä himself clearly tended to discount the older 'poorly described' study of Glazebrook & Thomson (1942) which lacked a placebo group, and which in any case failed to demonstrate a significant benefit for the males. Thus the evidence of any benefit for British male subjects rests almost entirely on the studies of Charleston & Clegg (1972) and of Baird et al (1979), neither of which seems a very reliable candidate for inclusion.…”
Section: Nutrition Discussion Forummentioning
confidence: 99%
See 2 more Smart Citations
“…In any case, this particular study yielded no evidence for benefit either from L-ascorbic acid, or from L-ascorbic acid plus Disoascorbic acid. Hemilä himself clearly tended to discount the older 'poorly described' study of Glazebrook & Thomson (1942) which lacked a placebo group, and which in any case failed to demonstrate a significant benefit for the males. Thus the evidence of any benefit for British male subjects rests almost entirely on the studies of Charleston & Clegg (1972) and of Baird et al (1979), neither of which seems a very reliable candidate for inclusion.…”
Section: Nutrition Discussion Forummentioning
confidence: 99%
“…In a long-lasting controversy, positive and negative findings are both newsworthy. For example, while Glazebrook & Thomson (1942), Walker el al. (1967), Carson et al (1975), Elwood et al (1976) and Tyrrell et al (1977) all explicitly drew rather negative conclusions as to their findings on vitamin C and the common cold, the papers were nevertheless written and published.…”
Section: Reply By Hemilämentioning
confidence: 99%
See 1 more Smart Citation
“…Truswell (25), referring to certain common cold studies, stated that, "there was no reduction in duration or severity with ascorbic acid as compared with placebo" (15,(31)(32)(33)(34)(35)(36)(37). Actually, Coulehan et al (35) found an 8% decrease in the "average duration of episodes" and a 12% decrease in "days in bed" among twins administered 0.5-1.0 g/d of the vitamin.…”
Section: Truswell's 1986 Minireviewmentioning
confidence: 99%
“…Six, large randomized trials of normally nourished subjects in Western countries, whose supplementation period ranged from 2 to 9 months, revealed no effect of vitamin C on common cold incidence (Anderson et al, 1972;Karlowski et al, 1975;Elwood et al, 1976;Ludvigsson et al, 1977;Pitt and Costrini, 1979;Briggs, 1984). However, studies of specific groups, such as subjects under heavy acute physical stress (Hemila, 1996) or British males with extremely low levels of vitamin C intake (Glazebrook and Thomson, 1942;Charleston and Clegg, 1972;Clegg and Macdonald, 1975;Baird et al, 1979), revealed significant reduction in common cold incidence with vitamin C supplementation. In addition, studies have consistently found reduced duration or severity of the common cold with vitamin C supplementation (Hemila and Douglas, 1999).…”
Section: Introductionmentioning
confidence: 99%